Tandem repeats modify the structure of the canine CD1D gene. (19th September 2012) - Looringh van Beeck, F. A.; Leegwater, P. A. J.; Herrmann, T.; Broere, F.; Rutten, V. P. M. G.; Willemse, T.; Van, I.
Summary Among the CD1 proteins that present lipid antigens to T cells, CD1d is the only one that stimulates a population of T cells with an invariant T‐cell receptor known as NKT cells. Sequencing of a 722 nucleotide gap in the dog (Canis lupus familiaris) genome revealed that the canine CD1D gene lacks a sequence homologous to exon 2 of human CD1D, coding for the start codon and signal peptide. Also, the canine CD1D gene contains three different short tandem repeats that disrupt the expected gene structure. Because canine CD1D cDNA lacks sequences homologous to human exon 2 and 3, the functionality of canine CD1d protein may be affected, and this could have consequences for the development and activation of canine NKT cells.